2019
DOI: 10.1111/anec.12688
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term repeatability of electrocardiographic criteria of left ventricular hypertrophy

Abstract: Background Left ventricular hypertrophy (LVH) is a marker of cardiac end‐organ damage and a risk factor for cardiovascular morbidity and mortality. Although clinical trials and cohort studies commonly use the electrocardiogram (ECG) for LVH assessment, the repeatability of ECG‐LVH criteria has not been sufficiently examined. Therefore, we evaluated the repeatability of ECG‐LVH criteria. Methods Participants (n = 63) underwent two standard ECGs at each of two visits, two weeks apart. The ECGs were processed cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…The Cornell voltage is currently one of the most widely used ECG indices of LVH. In the same study population, we previously reported that the ICC for the continuous Cornell voltage index was 0.97 (95% CI: 0.96–0.98) (Meyer et al., 2020). When comparing to the Peguero‐Lo Presti index, the Cornell voltage index showed similar repeatability (determined by the overlapping 95% confidence intervals).…”
Section: Discussionmentioning
confidence: 65%
“…The Cornell voltage is currently one of the most widely used ECG indices of LVH. In the same study population, we previously reported that the ICC for the continuous Cornell voltage index was 0.97 (95% CI: 0.96–0.98) (Meyer et al., 2020). When comparing to the Peguero‐Lo Presti index, the Cornell voltage index showed similar repeatability (determined by the overlapping 95% confidence intervals).…”
Section: Discussionmentioning
confidence: 65%
“…Left ventricular mass is measured by accurate techniques, such as echocardiography, computerized tomography, magnetic resonance, and three‐dimensional echocardiography. Electrocardiography (ECG) is the first‐choice technique for detecting left ventricular hypertrophy (LVH) in patients with hypertension due to its wide‐scale availability, low cost, repeatability, and established value prognostic 1‐3 . Current guidelines for diagnosis and treatment of hypertension strongly recommend ECG as the only examination to be performed in all hypertensive subjects for detection of LVH 4 .…”
Section: Introductionmentioning
confidence: 99%